Methodology for extending service life: application to large-scale excavation assets - Ferreira, Marie Clayre Freitas; Magno, Esmael de Miranda; Silva, Bruna Cristina da (Brazilian Journal of Production Engineering, 2026)
This paper presents the application of Life Data Analysis (LDA) as a tool for reliability assessment and optimization of replacement cycles of mechanical components in large‑scale electric excavators used in mining operations. The proposed methodology is based on the collection and treatment of historical operational data, statistical modeling using probabilistic distributions, and the analysis of the impact of extending asset service life on reliability and operational costs. The study was applied to the main mechanical systems (hoisting, digging, swing, and propulsion) of Caterpillar 7495HD and 7495HR large‑scale excavator models, using data from the period between 2020 and 2025. The results indicate that, for most of the components analyzed, it is possible to extend replacement cycles while maintaining reliability levels within previously established limits. The application of the methodology to a hoist gearbox demonstrated a 20% increase in service life, with a significant reduction in the number of preventive replacements. Financial projections indicate substantial potential gains resulting from reduced costs related to components, installation kits, and losses associated with equipment downtime, thereby demonstrating the technical and economic feasibility of the proposed approach.
Keywords: increased useful life; asset management; Reliability